Effects of spatial proximity to proposed electric power lines on residents' expectations, attitudes, and protest behavior: A replication study. (July 2019) - Mueller, Christoph Emanuel
Abstract: Governments and energy operators are frequently confronted with opposition to the construction of new high-voltage transmission lines. In this context, a recent experiment by Mueller et al. (2017) tested the so-called proximity hypothesis and found that spatial proximity to proposed transmission line corridor route alternatives significantly affected residents' likelihood of having negative risk expectations, showing low levels of support, and engaging in protest against the planned facility. Moreover, their findings suggest that the relationship between spatial proximity and the dependent variables is appropriately modeled by a distance decay function, showing that effects attenuate with increasing distance from the infrastructure site. Unfortunately, because of the fact that the study is the only one that has tested the proximity hypothesis in the context of planning new transmission lines so far, the existing evidence cannot be considered as a solid knowledge base. Therefore, to strengthen the reliability of the existing evidence, the natural experiment of Mueller et al. (2017) has to be replicated, which is the purpose of the present study. The findings of the replication clearly support the results provided by Mueller and colleagues and provide further empirical evidence that strengthens the proximity hypothesis in the context of power grid expansion. Highlights: Study replicates the natural experiment conducted by Mueller et al. (2017). Study estimates the effects of spatial proximity to proposed power lines. Data were collected after the announcement of corridor route alternatives. The findings of Mueller et al. (2017) could be confirmed by the replication. Proximity had effects on residents' risk expectations, attitudes, and behavior.